Revitalizing the Role of Women for the Effectiveness of Strategic Management of Sustainable Regional Development: Reconstruction of Gender Ideology in the Perspective of Islamic Law - Faiz Faricha; Abdul Halim (https://journal.metanusantara.com/jenius/index.php/jem, 2025)
The acceleration of sustainable regional development is often hampered by theological construction bias and managerial inefficiencies that limit the potential of women's human capital. This research aims to reconstruct gender ideology in the perspective of Islamic law and analyze strategies for revitalizing the role of women in regional development management. Using a qualitative approach with a socio-legal case study design, data was collected through in-depth interviews and focused discussions with key informants from elements of the management of KOPRI PMII, local government development planners (Bappeda), and Islamic law scholars/experts. The findings of the study reveal that there is an epistemological stagnation where the cadre curriculum is still dominated by domestic fiqh narratives that fail to legitimize women's public leadership. In addition, a significant capability gap was found between the high level of ideological militancy and the low technocratic competence in the digital era, which resulted in women's participation in development planning deliberations (Musrenbang) being trapped in the practice of tokenism or merely symbolic formalities. This study concludes that the effectiveness of regional strategic management demands the transformation of the women's movement from a textualist paradigm to a Mubadalah (mutuality) approach, accompanied by mastery of data-driven policy analysis to ensure substantive involvement in regional budget politics.